Pericardial Effusion as a Primary Manifestation of a Lung Adenocarcinoma - Egbe, Antoine; Tadesse, Eyouab; Ruffino, Catrina; Arshad, Khurram; Sandio, Aubin; Mozaffari, Ali; Subahi, Ahmed; Jamil, Mariam; Tynes, Donald; Delafontaine, Patrice (Cardiology and Cardiovascular Medicine, 2024)
Pericardial effusions are a frequent finding in everyday clinical practice, typicallyresulting from malignancy in developed countries. This presentation is generally a secondarymanifestation of malignancy, rather than the primary manifestation, as in this case of lungadenocarcinoma. An 85-year-old woman on 3L of home oxygen for chronic obstructivepulmonary disease with extensive smoking history presented to the emergency department withshortness of breath, along with a one week history of cough productive of clear sputum, bilaterallower extremity edema, decreased urine output and loss of appetite. Her family also reportedweight loss over the past year. CT(computed tomography) of the chest revealed moderatepericardial effusion, a 1.5cm pulmonary nodule and bilateral pleural effusions. Echocardiogramshowed a large pericardial effusion but no evidence of hemodynamic compromise. Due to thefindings of moderate pericardial effusion, shortness of breath and extensive smokinghistory,1.5cm pulmonary nodule and reports of weight loss, a decision was made to drain thepericardial effusion despite hemodynamic stability. Pericardial fluid cytology returned positive formalignancy with tumor marker PDL-1(programmed death ligand-1), consistent with a non-smallcell lung cancer. After readmission with shortness of breath, the deteriorating patient was placedon comfort care, passing away only 26 days after her initial presentation. Malignancy can causepericardial effusion in various ways (commonly metastasis) with poor prognosis, despite oftenstraightforward management with pericardiocentesis as seen in this patient. In this case,unusually, the primary manifestation of advanced lung adenocarcinoma was pericardial effusionpresenting with shortness of breath without hemodynamic instability. Pericardial fluid cytologyremains the cornerstone of diagnosis, but considering possible false negatives, clearerrecommendations for intrapericardial therapeutic approaches in similar clinical scenarios are needed to address recurrent, malignant pericardial effusions, particularly when it occurs as theprimary manifestation.